Factors Associated with Undernutrition of Children Admitted in Koshi Zonal Hospital Nutritional Rehabilitation Home - Mandal, Punam Kumari (Tribhuvan University Journal, 2018)
This study follows mixed method with the objective to assess the factor associated with undernutrition among the children admitted in NRH. This study was conducted in Koshi Zonal Hospital. The study covers the children admitted in NRH and their mothers from 14th March to 28th May 2016 with sample size of 20. The study shows the highest number of children belonged to disadvantaged non Dalit Terai caste groups (35 %) and majorities (45 %) of the mothers found to be illiterate. A statistically significant difference was observed between the mean weight at discharge and the mean weight at admission for the study group (t=2.98, P<0.008, CI 0.46-2.65). The cause of malnutrition was lack of nutritious food, poverty, unhygienic condition at home, diseases and lack of nutritious food during pregnancy. There were knowledge gap regarding the nutrition, causes of malnutrition and its prevention, balanced diet and therapeutic food among the mothers. An urgent need to link these centers with community-based models was felt necessary to improve health education measures and awareness.